LEGAL PROTECTION FOR DECEASED RECIPIENTS OF NOTARIAL WILLS - Ira Sudjono; Aloysius Uwiyono; Endang Pandamdari (Transpublika Publisher, 2024)
The objective of this study is to examine the legal protection provided to the community in relation to the copies of wills created by deceased notaries. This research falls under the category of normative law and adopts both a statutory and case-based approach. The study utilizes primary and secondary data, drawing from various legal sources including primary, secondary, and tertiary legal materials. The findings reveal that the submission of the Notarial Protocol should be completed within 30 days, accompanied by an official report signed by both the submitter (heir) and the recipient (notary). It is not uncommon for the family and heirs of a deceased notary to lack understanding of the rules and procedures pertaining to the transfer of notary protocols. This knowledge gap can be attributed to the insufficient education provided to the notary's family, heirs, employees, as well as the wider community by the notary themselves, notary organizations, and the Ministry of Law and Human Rights. Additionally, there is a legal vacuum in the judicial system concerning potential issues that may arise during the submission process of notary protocols. Therefore, it is imperative to reformulate the regulations governing the submission of notary protocols, including the implementation of sanctions for negligent heirs and temporary notary officials who fail to submit the protocols of deceased notaries. Furthermore, the introduction of electronic-based storage systems for notary protocols should be considered to ensure legal certainty for the public.